Bolometric detectors for EBEX: a balloon-borne cosmic microwave background polarimeter. - Hubmayr, Johannes (2009)
University of Minnesota Ph.D. dissertation. December 2009. Major: Physics. Advisor: Hans George Othmer. 1 computer file (PDF); xii, 124 pages, appendices A-C. We discuss the design and performance of arrays of millimeter-wave, bolometeric detectors for EBEX, the E and B Experiment. EBEX is a balloon-borne telescope designed to measure the polarization in the cosmic microwave background (CMB) radiation with 8 arc-minute resolution at 150, 250 and 410 GHz during a 14-day long duration balloon flight in Antarctica. On June 11, 2009 EBEX launched an engineering test flight from NASA's Columbia Scientific Ballooning Facility (CSBF) achieving 10 hours at float altitudes of 115,000 ft. EBEX is the first experiment to successfully operate transition edge sensor (TES) bolometers readout by superconducting quantum interference devices (SQUIDs) from a balloon platform. We present the EBEX instrument design, review TES bolometer and SQUID theory of operation and elaborate on frequency domain multiplexing. Following the analysis of the detector and readout system, we detail measurements that characterize the bolometers and conclude with a discussion of the EBEX receiver optical efficiency and in-flight bolometer loading during the engineering flight.